EFL Learners’ Perspective on Corrective Feedback - Muhammad Fahruddin Aziz; Herlandri Eka Jayaputri (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
The present research is designed to investigate the attitudes of EFL Learner concerning corrective feedback. This research additionally analyses students’ characteristics that tend to receive offline or online corrective feedback and analyses the approach of sending feedback adjusted to learners’ exact needs. 75 research respondents were enrolled from Biak’s High School of Law, Papua. The researchers handed out questionnaires directly to the 5th and 7th semester students during lectures. There were eight questions provided for students to choose regarding corrective feedback. The findings of this research indicate that online or offline corrective feedback is very important for students because it can help students determine the correct linguistic form. Most students feel that corrective feedback is quite helpful for them because it can encourage students’ desire to learn. In addition, they also feel that corrective feedback can improve the learning process. However, some students feel that they are not serious enough when receiving teacher’s feedback because they have not been able to realize which ones can hinder or improve the language learning process. It seems clear that most students like feedback both offline and online. Thus, the results of this research generally confirm that students feel corrective feedback provides benefits in improving the learning process.